Impact of Compensation and Work Stress on Employee Performance - Achmad Daengs GS; Enny Istanti; Nisa Widhawati (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This study aims to examine the impact of compensation and work stress on employee performance at a branch office. The research population consisted of 37 employees, and the sample used in the study was also drawn from the same group. Data analysis was conducted using multiple linear regression with the assistance of SPSS 18 statistical software. The findings revealed that both compensation and work stress significantly affect employee performance. Specifically, the results indicate that higher compensation and reduced work stress lead to improved employee performance. Based on these findings, the author recommends that the company continue to prioritize compensation adjustments and work stress management to ensure ongoing improvements in employee performance. By addressing these factors, the company will be better positioned to achieve its organizational goals. This study underscores the importance of a supportive work environment where employees feel fairly compensated and experience manageable stress levels, ultimately enhancing productivity and contributing to the overall success of the organization.